Science teacher as classroom manager in online classes - Margaritta L. Hermoso; Jaime C. Erlano, Jr.; Dhafney I. Gonzaga; Michael Clyde S. Lepasana; Neña Jane C. Lumen; Joje Mar P. Sanchez (Institute of Advanced Engineering and Science, 2022)
Exploratory sequential mixed research was conducted to characterize science teachers' experiences as classroom managers in their online classes. There were 15 science teachers from elementary and secondary schools in Cebu, Philippines, participated in the phenomenological study, and 30 teachers responded to the developed tool on their management and its effect on students’ performance. Thematic analysis of the interview results unveiled a series of stages, including a different start of the school year and reintegration of online management skills that eventually led to autonomy in online classes and satisfying academic outcomes. Further exploration of the quantitative aspect of the study revealed that they have very good management, which has led to a good effect on students' performance. The different innovations in classroom management strategies by science teachers led to effective online classes. Training on proactive management and positive feedbacking are recommended.